Analisis Faktor yang Mempengaruhi Laju Pertumbuhan Sektor Pertanian pada PDRB Kabupaten Klungkung - SOPAN, MICHAEL; BUDIASA, I WAYAN; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
Analysis of Factors Affecting the Growth Rate of the Agricultural Sector in the GRDP of Klungkung Regency The purpose of this study was to determine the factors that influence the growth rate of the agricultural sector in the GRDP of Klungkung Regency. The variables used in this study were dry milled unhulled rice production, rice field area, and labor. The research data used is data contained in related agencies from 2011-2019 for 9 years and is taken from agencies such as the Central Statistics Agency, the Klungkung Regency Agriculture Service, and others. This research was conducted by means of multiple linear regression analysis. The results showed that the growth rate of the agricultural sector in the GDRP of Klungkung Regency was influenced by various factors consisting of the production of milled dry unhulled rice, rice field area, and agricultural labor. The results of this study mean that the more production of milled dry unhulled rice, the more paddy fields owned by the farmers and the more agricultural labor, the higher the growth rate of the agricultural sector in the GDRP of Klungkung Regency. Based on the results of the study, it is recommended for local governments to increase agricultural sector revenues starting with protecting and increasing the area of ??rice fields, developing labor productivity to increase dry milled grain production so that the GRDP growth rate of the agricultural sector in Klungkung Regency can increase.